Development of pistachio (pistacia vera L.) spread. - Shakerardekani, Ahmad; Karim, Roselina; Mohd Ghazali, Hasanah; Chin, Nyuk Ling (Wiley, 2013)
Pistachio nut (Pistacia vera L.) is one of the most delicious and nutritious nuts in the world. Pistachio spreads were developed using pistachio paste as the main component, icing sugar, soy protein isolate (SPI), and red palm oil (RPO), at different ratios. The highest mean scores of all the sensory attributes were depicted by spreads that were made without addition of SPI. It was found that the work of shear was 0 to 11.0 kg s for an acceptable spread. Sensory spreadability, overall texture, spreadability, and overall acceptability were negatively correlated (R > 0.83) with the work of shear of spreads. The findings indicated that the presence of RPO had a direct effect on the viscoelastic behavior of the pistachio spreads. The a values, which are related to the green color of the pistachio product ranged from 1.7 to 3.9 for spread without addition of RPO, and 4.0 to 5.3 in the presence of RPO.